The Susceptibility of Pea (Pisum sativum L.) to Simulated Mesotrione Residues as Affected by Soil pH Manipulation - Ana Pintar; Zlatko Svečnjak; Josip Lakić; Ivan Magdić; Dragojka Brzoja; Klara Barić (Agriculture, 2021)
Variations in soil pH have been shown to affect mesotrione adsorption, which in turn, may have an impact on crop susceptibility. Therefore, a greenhouse experiment was conducted to evaluate the effect of simulated mesotrione residues on pea crop grown in the typical agricultural soil (gleysol) of north-western Croatia. The soil pH was manipulated to obtain neutral (pH 7.0) and acidic (pH 5.0) values. Simulated mesotrione residues were 1.1, 2.3, 4.5, 9.0, 18, 36 and 72 g a.i. ha−1. Crop visual injuries as well as reductions in chlorophyll fluorescence and aboveground dry biomass were higher at pH 7.0 than at pH 5.0. With increasing mesotrione residues, the reductions in chlorophyll fluorescence ranged from 38.8% to 89.7% at pH 5.0 and from 63.7% to 99.3% at pH 7.0. Compared to chlorophyll fluorescence, the reductions in dry biomass were smaller and ranged from 49.2% to 96.8% at pH 7.0 and from 32.0% to 82.6% at pH 5.0 for the mesotrione residues from 1.1 to 72 g a.i. ha−1. These results indicate that soil pH is an important factor determining the susceptibility of pea crop to simulated mesotrione residues.